THE ROLE OF ENGLISH AS GLOBAL LANGUAGE - Sofyan, Nurlaily (EDUKASI, 2021)
English is now used as a lingua franca, most of the native and non-native speakers of English are using English as their mode of communication in their business matters or business organizations. English language is spread all over the world into almost all the fields such as science, engineering and technology, medicine, trade and commerce, scientific research, education, tourism, internet, banking, business, advertising, film industry, transportation, pharmacy and to name a few. The international expansion of English has been predicted and promoted regularly by leaders on both sides of the Atlantic over the past 200 years. In October 1934 the Carnegie Foundation sponsored a conference in New York on ‘The use of English as a world language’. ELF is used in a number of fields in which English is used as the mutual language of choice, such as science, politics, business, and education. The materials of higher education in English is to make it available for the learners and the teachers wherever they are located on this earth, most of the students, teachers and research scholars make use of this opportunity to enhance their qualification as well as knowledge. The widespread of English as an international language and with the advent of the internet as a mode of fast communication channel which has no boundaries, both are mutually enforcing novel trends and bringing tremendous changes in this age of globalization. English is the only language that is internationally spoken and accepted. Furthermore, the impact of the English language on the internet has been disclosed above and it also has been proved that there are many websites using English as their medium of communication. Even though there are certain fields that are not mentioned, it seems that English plays a dominant in those areas also.